ANALYSIS OF COSTS AND PROFITABILITY IN TRADE ORGANIZATIONS - Pashakhodzhayeva , Dzhamilya (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
The article focuses on the analysis of costs and profitability in trade organizations as a critical component of financial performance assessment. The research explores the relationship between cost structures, pricing strategies, and profitability indicators. Using analytical and comparative methods, the study evaluates key cost drivers and their impact on gross margin and overall financial results. The results highlight the importance of systematic cost analysis for improving profitability and ensuring sustainable development of trade organizations. The paper offers practical recommendations for optimizing cost structures and enhancing financial efficiency in a competitive market environment.